Proses Komunikasi Interpersonal dalam Ta'aruf di Kota Banda Aceh - Ridwansyah Ridwansyah (Jurnal Komunikasi Global, 2018)
Ta'aruf is an introductory method in Islam between men and women who want to find their partner to get married. Due to some strict barriers to know the opposite sex, ta'aruf becomes a solution in knowing the prospective partner before marriage. This study focused on the ta'aruf process before marriage and described the process of the interpersonal communication developments. It aims to analyze the process of the interpersonal communication of married couples through ta'aruf in Banda Aceh. Social Penetration Theory was used to explain the stage of the relationship development in ta'aruf. Data were collected using interviews with five married couples undergoing ta'aruf process who were selected with purposive sampling technique. The results of this study indicated that couples who performed ta'aruf only went through the orientation stage. This is due to the constraints in ta'aruf limiting the process of interpersonal communication they underwent. The exploratory affective exchange, affective exchange, and stable exchange they experienced after they got married.